PENGEMBANGAN DAN IMPLEMENTASI LKPD BERBASIS KONTEKSTUAL PADA PEMBELAJARAN MATEMATIKA DI SMP 17 BANDA ACEH - lindayani (Jurnal Humaniora Pendidikan (JHP), 2025)
This study aims to develop and implement a contextual-based Student Worksheet (LKPD) in mathematics learning on number pattern material at SMP 17 Banda Aceh. The research employed a Research and Development (R&D) method using the ADDIE model, limited to the analysis, design, and development stages. The subjects consisted of two material experts, one media expert, and eighth-grade students. Data were collected through validation questionnaires and analyzed quantitatively using percentage techniques. The results showed that the developed LKPD achieved a material validation score of 88% and a media validation score of 83%, both categorized as very valid. Therefore, the contextual-based LKPD is feasible for use in mathematics learning and has the potential to improve students’ conceptual understanding.